French Economic and Monetary Policies in Francophone Africa:: A Barrier to Economic Development in the Central and West African Monetary Zones - DZEKASHU, WILLIAM (Archives of Business Research, 2021)
Since granting independence to her former colonies (especially the countries in the West and Central Africa subregions), France has maintained tight economic, political, and to a great extent, social control over their internal and external affairs. These continued ties with France have become the subject of contentious debates (previously considered taboo) among scholars in recent times, evidenced in the development of activism in Africa and continental Europe where the former has been sensitized or radicalized about France’s exploitative approach to economic partnership. The economies of these African nations have suffered stagnation and retrogression in contrast to their non-French-influenced neighbors. This essay employs a literature review to assess the impact of French hegemony over these former colonies, therefore providing a cogent argument for the abolition of the monetary agreement in favor of a local currency, and cessation of political dependencies that also carry a negative stigma. Intellectuals and politicians have argued that the continued use of the CFA franc currency (a relic of colonialism with a different twist) is exploitative; recognized even by French politicians who have appealed to their government to employ moral and ethical considerations to desist from the persistent exploitation of Africa. Social movements have developed today in demanding that African nations still using this currency should withdraw from the agreements due to the severe negative effects on economic development.